Optimalisasi Peletakan Posisi Access Point Pada Jaringan WI-FI Menggunakan Metode Simple Random Sampling Dan Coverage Visualization Di Fakultas Teknik Universitas Riau - Ryant Pratama; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
It require good technique of access point location placement to obtain good level signal. Proper placement of access point can determine the range of coverage area obtained by using parameter from access point. The purpose of this study is to do optimization of access point location placement to reduce blank spot in Engineering Faculty of Universitas Riau. Current scope of Wi-Fi signal coverage area is still not enough to cover all areas in Engineering Faculty of Universitas Riau. There are some adjacent access point locations that needed to optimization to obtain good quality signal and better access point location can be obtained. inSSIDer application is used to identify the Wi-Fi signal strength, Ekahau HeatMapper application is used to identify coverage area, and Ekahau Site Survey application is used to implement optimization. Based on calculation, measurement, and implementation result by using Simple Random Sampling Method can be obtained dominant result of signal strength is ≥-45dBm. It can be determined that causative factors of less optimal from coverage area scope is not only by building construction, but also the placement between access points can also affect reobtained coverage area.Keywords : Access Point, Optimization, Coverage Area, Simple Random Sampling Method.